Arthroscopic management of a lateral glenohumeral ligament rupture in two dogs - Pettitt, R. A.; Innes, J. F. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Tears to the lateral glenohumeral ligament appear to be uncommon in dogs. Two Labrador Retrievers were arthroscopically diagnosed with lateral glenohumeral ligament tears of the shoulder. Both cases failed to respond to conservative management. Surgical stabilisation of the lateral aspect of the shoulder joint was achieved using an arthroscopically placed suture using a hanging limb technique. Lameness resolved in both cases.
Keywords: Lateral glenohumeral ligament; arthroscopy; dog